[Arctic Ocean From Húsavík] - Streng, Evelyn Fiedler (1975)
Photograph of the Arctic Ocean from Húsavík, Iceland. The light blue ocean stretches across the photograph, surrounded by grass and grey rock covered land to the left and a snow capped mountain range in the background. The sky is covered in a wall of white clouds.